2019
DOI: 10.1007/s00430-019-00645-2
|View full text |Cite
|
Sign up to set email alerts
|

Human adenovirus binding to host cell receptors: a structural view

Abstract: Human Adenoviruses (HAdVs) are a family of clinically and therapeutically relevant viruses. A precise understanding of their host cell attachment and entry mechanisms can be applied in inhibitor design and the construction of targeted gene delivery vectors. In this article, structural data on adenovirus attachment and entry are reviewed. HAdVs engage two types of receptors: first, an attachment receptor that is bound by the fibre knob protein protruding from the icosahedral capsid, and next, an integrin entry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 60 publications
0
60
0
Order By: Relevance
“…Other viruses that predispose the host for secondary bacterial infections include respiratory syncytial virus (RSV), rhinovirus (RV), human coronavirus, parainfluenza virus and adenovirus (AV) ( Falsey et al., 2013 ). Whereas parainfluenza virus also uses host sialic acids to attach to cells, syncytial virus, rhinovirus, parainfluenza virus and adenovirus utilize diverse attachment receptors ( Moscona, 2005 ; Bochkov and Gern, 2016 ; Battles and McLellan, 2019 ; Stasiak and Stehle, 2020 ). The novel coronavirus SARS-CoV-2 binds the cellular receptor Angiotensin-converting enzyme 2 (ACE2) to cause coronavirus disease 2019 (COVID-19) ( Yan et al., 2020 ).…”
Section: The Clinical Situation—coinfections In Cap and Hapmentioning
confidence: 99%
“…Other viruses that predispose the host for secondary bacterial infections include respiratory syncytial virus (RSV), rhinovirus (RV), human coronavirus, parainfluenza virus and adenovirus (AV) ( Falsey et al., 2013 ). Whereas parainfluenza virus also uses host sialic acids to attach to cells, syncytial virus, rhinovirus, parainfluenza virus and adenovirus utilize diverse attachment receptors ( Moscona, 2005 ; Bochkov and Gern, 2016 ; Battles and McLellan, 2019 ; Stasiak and Stehle, 2020 ). The novel coronavirus SARS-CoV-2 binds the cellular receptor Angiotensin-converting enzyme 2 (ACE2) to cause coronavirus disease 2019 (COVID-19) ( Yan et al., 2020 ).…”
Section: The Clinical Situation—coinfections In Cap and Hapmentioning
confidence: 99%
“…Subsequent work showed that some but not all of the EKC-associated HAdVs bind to sialic acid-expressing cell surface glycans [ 85 ], and that various multivalent sialic acid constructs could block binding [ 84 , 86 , 87 , 88 , 89 , 90 , 91 ]. Sites on the fiber knob that bind to the various potential adenovirus receptors have been mapped in exquisitely detailed structural studies [ 92 ]. Binding is not only specific to HAdV species [ 76 ], but also differs within HAdV species [ 65 , 77 , 93 , 94 ].…”
Section: Corneal Epithelial Cell Tropism and Receptorsmentioning
confidence: 99%
“…An adenovirus is a non-enveloped double-stranded DNA virus with a symmetrical icosahedral structure ( 9 ). The genome is ~36 kb in length and can encode >40 gene products ( 10 ).…”
Section: Oncolytic Adenovirusmentioning
confidence: 99%